2023
DOI: 10.1007/s10433-023-00771-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing retirement ages in Denmark: Do changes in gender, education, employment status and health matter?

Abstract: Recent studies report significant increases in retirement ages over the past two to three decades in most countries in the Organization for Economic Co-operation and Development—increases that research has attributed mainly to changes in the legislative frameworks for retirement in these countries. Using unique data from the Danish Longitudinal Study of Ageing, this study investigates whether and, if so to what extent, changes to the workforce in terms of gender, education, employment status (employed or self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Some studies have found that education can have a direct effect on retirement ages, even despite the long period of time between entering and exiting the labour market (Hardy 1984;Venti/ Wise 2015). Most studies, however, emphasise that education usually sets the stage for subsequent opportunities in life and work, and that the impact of education on activity at older ages is mediated through, amongst other factors, occupational status, income, wealth, working conditions, and health (Amilon/Larsen 2023;Komp et al 2010;Rohrbacher/Hasselhorn 2022;Thern et al 2022;Turek/Henkens 2023). In particular, educational inequalities in health tend to increase with age (Leopold 2018), making the possibilities for extending working lives more unequal as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that education can have a direct effect on retirement ages, even despite the long period of time between entering and exiting the labour market (Hardy 1984;Venti/ Wise 2015). Most studies, however, emphasise that education usually sets the stage for subsequent opportunities in life and work, and that the impact of education on activity at older ages is mediated through, amongst other factors, occupational status, income, wealth, working conditions, and health (Amilon/Larsen 2023;Komp et al 2010;Rohrbacher/Hasselhorn 2022;Thern et al 2022;Turek/Henkens 2023). In particular, educational inequalities in health tend to increase with age (Leopold 2018), making the possibilities for extending working lives more unequal as well.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence on these trends, however, is thus far mixed. Country-specific factors are likely to play an important role: while in some countries educational inequalities in exit and retirement ages increased, they decreased in other countries (Amilon/ Larsen 2023;Polvinen et al 2022;Riekhoff/Kuitto 2022;Rutledge 2018;Turek et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Today, most of the research and data on differences in labour force participation and age at retirement also focus on SES indicators, such as education. These have shown, for example, that in Denmark the least-educated are less likely to be employed (own analyses of Eurostat data 4 ) and that they retire earlier than more-educated groups, although the difference has been decreasing (Amilon and Larsen 2023). By reducing the importance of the standard retirement age, these patterns could to some extent mitigate the increasing gap in survival between household types as less-educated individuals are also more likely to be single, but to the disadvantage of other dimensions such as earnings.…”
Section: Consequences For Retirement Agementioning
confidence: 99%